2014
DOI: 10.1021/ja5051633
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemistry with Metallosupramolecular Polymers

Abstract: ABSTRACT:The transduction of mechanical force into useful chemical reactions is an emerging design approach to impart soft materials with new functions. Here, we report that mechanochemical transductions can be achieved in metallosupramolecular polymers. We show that both reversible and irreversible reactions are possible and useful to create mechanically responsive materials that display new functions. The metallopolymer studied was a crosslinked network assembled from a europium salt and a telechelic poly(et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
165
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 220 publications
(170 citation statements)
references
References 38 publications
1
165
1
3
Order By: Relevance
“…In the context of healable systems, a pioneering example was reported by Greenland et al [98], who used computational models to predict that pyrene residues could be alternated with electron-poor aromatic moieties to create stacked systems; in a first experimental embodiment, the authors used this framework to impart dynamic cross-links to a rubbery matrix ( Figure 10a). As demonstrated by several groups, the formation of stacks or segregated systems containing the supramolecular motifs is capital to bestow sufficient mechanical properties to otherwise weak supramolecular materials [34,86,99]. This feature also played a central role in the determination of the association in the case of these -bonded materials, as shown by spectroscopy on model molecular equivalents.…”
Section: Supramolecular Polymers Based On  Interactionsmentioning
confidence: 89%
“…In the context of healable systems, a pioneering example was reported by Greenland et al [98], who used computational models to predict that pyrene residues could be alternated with electron-poor aromatic moieties to create stacked systems; in a first experimental embodiment, the authors used this framework to impart dynamic cross-links to a rubbery matrix ( Figure 10a). As demonstrated by several groups, the formation of stacks or segregated systems containing the supramolecular motifs is capital to bestow sufficient mechanical properties to otherwise weak supramolecular materials [34,86,99]. This feature also played a central role in the determination of the association in the case of these -bonded materials, as shown by spectroscopy on model molecular equivalents.…”
Section: Supramolecular Polymers Based On  Interactionsmentioning
confidence: 89%
“…Their study showed that metallo-supramolecular polymers based on macromonomer 5 (a telechelic poly(ethylene-co-butylene) with Mebip ligands at the termini) and the europium salt Eu(ClO 4 ) 3 ( Figure 23a) are mechanoresponsive. [86,87] The Eu 3+ :Mebip complexes serve both as mechanically responsive binding motifs and built-in optical probes that can monitor the extent of (dis)assembly due to their characteristic photoluminescent properties. Dose-dependent and reversible metal-ligand dissociation occurs upon exposure to ultrasound in solution (Figure 23b, 24a).…”
Section: Metal-ligand Interactionsmentioning
confidence: 99%
“…This disassembly is only possible with a high-molecular weight supramolecular entity, thus again showing the same size dependence as reported for covalent polymer mechanophores. The strength of the metal-ligand interaction is also critical, as polymers that contain more strongly coordinating ligands do not dissociate under irradiation [88]. Interestingly, the authors searched for mechanically healable responses and, to this end, polymer films were cut into pieces, gently pressed and exposed to ultrasound, while either directly immersed in a CH3CN solution or in a sealed bag.…”
Section: Fig 14mentioning
confidence: 99%